Gambaran Perilaku Gaya Hidup Sehat Pada Remaja di Ungaran Kabupaten Semarang - Fadhilatul Tufaidah; Puji Purwaningsih; Trimawati Trimawati (Indonesian Journal of Nursing Research (IJNR), 2019)
Unhealthy lifestyles such as lack of physical activity, eating unhealthy foods, and stress in teenagers are now increasing. The presence of unhealthy behavior in teenagers can be bad for their health, one of which is the increasing of risk of non-communicable diseases. Therefore applying healthy lifestyle behaviors in teenagers is very important to prevent the occurrence of non-communicable diseases in the future.The purpose of this study was to describe healthy lifestyle behaviors in teenagres which included responsibility for health, physical activity, nutrition, spiritual growth, interpersonal relations, and stress management. This study uses descriptive method with cross sectional approach. The study population was 1.445 adolescents. The sampling technique used proportional random sampling. Total samples were 314 teenagers. Data collection used the Healthy Promotion Lifestyle Profile -II questionnaire. Data analysis used Frequency Distribution. The results showed that the majority of teenagers had fairly good healthy lifestyle behaviors of 226 people (72%), quite good on aspect of health responsibility of 214 people (62.8%), good in healthy lifestyle behavior in aspect of physical activity of 160 people (51%), quite good in the nutritional aspect of 159 people (50.6%), goodin the aspect of spiritual growth of 205 people (65.3%), good in aspect of interpersonal relations of 222 people (70.7%) , and good in the stress management aspect of 211 people (67.2%). An advice for teenagers is to use this research results as an input on healthy lifestyle behaviors that can be carried out and applied in daily lifeKey words: Behaviour, Healthy Lifestyle, Teenager